First report of Klebsiella pneumonia carbapenemase-producing Pseudomonas aeruginosa isolated from burn patients in Iran: phenotypic and genotypic methods - Lari, Abdolaziz Rastegar; Azimi, Leila; Rahbar, Mohammad; Alaghehbandan, Reza; Sattarzadeh-Tabrizi, Mahboobeh (German Medical Science GMS Publishing House, 2014)
[english] Wound infection associated with carbapenem-resistant in burn patients is a growing problem. One of the main mechanisms of resistance to carbapenem antibiotics is the ability of to produce carbapenemase enzymes. carbapemenase (KPC) is an important type of carbapenemase which can hydrolyze carbapenem antibiotics. The Modified Hodge Test (MHT) and boronic acid as a KPC inhibitor are two phenotypic methods used for detection of carbapenemase. The sensitivity and specificity of these two phenotypic tests for the identification of KPC can be measured by PCR.In this study, 241 strains were isolated from wounds of hospitalized burn patients. Carbapenem-resistant isolates were determined by the disk diffusion method. KPC-producing carbapenem-resistant strains were examined using the Modified Hodge Test, followed by boronic acid. Further, strains with positive responses to MHT and boronic acid tests were analyzed with the PCR molecular method. One hundred eighty-six of 241 isolates were resistant to carbapenems and 75 were positive in the MHT. Three exhibited an at least 5-mm diameter difference when meropenem was combined with boronic acid vs meropenem alone in the boronic acid test. Two strains had a specific band with primer No.1 after gel electrophoresis. This study showed that MHT, despite excellent sensitivity, has variable specificity independent of bacterial species. Further, the use of KPC inhibitors such as boronic acid did not yield favorable sensitivity and specificity among the specimens from Iranian patients. Thus, it seems that sequencing after PCR should be considered the gold standard for the detection of KPC-producing .